An International Commentary on Dysphagia and Dysphonia During the COVID-19 Pandemic - Miles A; McRae J; Clunie G; Gillivan-Murphy P; Inamoto Y; Kalf H; Pillay M; Pownall S; Ratcliffe P; Richard T; Robinson U; Wallace S; et al. (Springer Nature, 2022)
COVID-19 has had an impact globally with millions infected, high mortality, significant economic ramifications, travel restrictions, national lockdowns, overloaded healthcare systems, effects on healthcare workers’ health and well-being, and large amounts of funding diverted into rapid vaccine development and implementation. Patients with COVID-19, especially those who become severely ill, have frequently developed dysphagia and dysphonia. Health professionals working in the field have needed to learn about this new disease while managing these patients with enhanced personal protective equipment. Emerging research suggests differences in the clinical symptoms and journey to recovery for patients with COVID-19 in comparison to other intensive care populations. New insights from outpatient clinics also suggest distinct presentations of dysphagia and dysphonia in people after COVID-19 who were not hospitalized or severely ill. This international expert panel provides commentary on the impact of the pandemic on speech pathologists and our current understanding of dysphagia and dysphonia in patients with COVID-19, from acute illness to long-term recovery. This narrative review provides a unique, comprehensive critical appraisal of published peer-reviewed primary data as well as emerging previously unpublished, original primary data from across the globe, including clinical symptoms, trajectory, and prognosis. We conclude with our international expert opinion on what we have learnt and where we need to go next as this pandemic continues across the globe.
Keywords: COVID-19; Deglutition; Dysphagia; Dysphonia; ICU; Voice; Humans; COVID-19; Pandemics; Dysphonia; Deglutition Disorders; Communicable Disease Control